A coupled hygrothermo-mechanical viscoelastic analysis of multilayered composite plates for long-term creep behaviors. (15th June 2020) - Nguyen, Sy-Ngoc; Lee, Jaehun; Han, Jang-Woo; Cho, Maenghyo
Abstract: This paper investigates the coupling hygrothermo-mechanical behaviors of viscoelastic composite laminated plates by using a higher-order zigzag theory. All in-plane displacement, temperature, and moisture fields through the thickness are superimposed by the local linear zigzag terms on a global cubic polynomial distribution. The Laplace transform is employed to avoid suche time-dependent integration of a viscoelastic constitutive equation as well as to improve accuracy and efficiency. Thereby, all formulations are simplified in the Laplace domain. The hygrothermal variational principle is employed to determine the temperature and moisture distributions through the thickness. Then, viscoelastic relaxation moduli with various hygrothermal shift factors in each layer are calculated in the general form of Prony series. The final numerical results of stresses and deformations are obtained by using inverse Laplace techniques. To demonstrate the efficiency and accuracy of the proposed theory, some numerical examples for long-term creep process are performed. The proposed theory shows powerfully application for the prediction of fully coupled hygro-thermo-mechanical behaviors for thick viscoelastic composite laminates. Moreover, it can handle partial problems such as thermal conductivity, hygral absorption, thermo-elastic, thermo-viscoelastic analyses.